EFFECTS OF COOPERATIVE LEARNING MODEL TYPE NUMBERED HEADS TOGETHER USING SIMULATION MEDIA PHET AND ACTIVITIES TOWARD STUDENT RESULTS - Fitri Mawaddah Lubis; Mara Bangun Harahap (Jurnal Pendidikan Fisika, 2015)
This study aimed to analyze the differences in learning outcomes of students taught by cooperative learning model NHT using simulation PhET and conventional learning, analyzing the differences in learning outcomes of students who have high activity and low activity, as well as the  interaction between learning model with the level of student activity in  influencing the outcome students learn physics. This research is a quasi experimental. The population in this study were students of class X SMK Tritech Informatika Medan. The tests were used to obtain the data is in the form of multiple choice. Test requirements have been carried out in the form of normality and homogeneity, which showed that the normal data and homogeneous. The data were analyzed using Anova analysis of two paths. The results showed that: The physics learning outcomes of students who use cooperative learning model NHT using PhET simulations media is better than students who use conventional learning models. The physics learning outcomes of students who have high learning activities is better than students who have Low learning activities. There is an interaction between cooperative learning model NHT PhET simulations using the media and the level of learning activity in influencing student learning outcomes. Average increase learning outcomes in the control class is greater than the experimental class.